Patient experience and challenges in group concept mapping for clinical research - Mills, Geoffrey D. (J Patient Rep Outcomes, 2019)
BACKGROUND AND OBJECTIVE: Group concept mapping (GCM) is a research method that engages stakeholders in generating, structuring and representing ideas around a specific topic or question. GCM has been used with patients to answer questions related to health and disease but little is known about the patient experience as a participant in the process. This paper explores the patient experience participating in GCM as assessed with direct observation and surveys of participants. METHODS: This is a secondary analysis performed within a larger study in which 3 GCM iterations were performed to engage patients in identifying patient-important outcomes for diabetes care. Researchers tracked the frequency and type of assistance required by each participant to complete the sorting and rating steps of GCM. In addition, a 17-question patient experience survey was administered over the telephone to the participants after they had completed the GCM process. Survey questions asked about the personal impact of participating in GCM and the ease of various steps of the GCM process. RESULTS: Researchers helped patients 92 times during the 3 GCM iterations, most commonly to address software and computer literacy issues, but also with the sorting phase itself. Of the 52 GCM participants, 40 completed the post-GCM survey. Respondents averaged 56 years of age, were 50% female and had an average hemoglobin A1c of 9.1%. Ninety-two percent (n = 37) of respondents felt that they had contributed something important to this research project and 90% (n = 36) agreed or strongly agreed that their efforts would help others with diabetes. Respondents reported that the brainstorming session was less difficult when compared with sorting and rating of statements. DISCUSSION: Our results suggest that patients find value in participating in GCM. Patients reported less comfort with the sorting step of GCM when compared with brainstorming, an observation that correlates with our observations from the GCM sessions. Researchers should consider using paper sorting methods and objective measures of sorting quality when using GCM in patient-engaged research to improve the patient experience and concept map quality.